Finance for Food - Köhn, Doris (Springer Nature, 2014)
Development Economics; Agricultural Economics; Finance, general; Economic Growth; Macroeconomics/Monetary Economics//Financial Economics; Microfinance; Rural Finance; Agricultural Finance; Rural Development; Developing Countries